Urban streams as focal points of urban regeneration: The area of Konstantinidis stream in Toumba, Thessaloniki - Kastanidou Symela; Katsavounidou Garyfallia (E3S Web of Conferences)
Nowadays, the concept of Green Infrastructure (GI) is having a big impact when it comes to planning cities and to policymaking, due to the need for substantial rethinking of urban development and for a contemporary way to respond to the current environmental global challenges. Urban rivers and streams are important elements of GI and their ecological restoring can promote biodiversity and climate adaptation, while improving quality of life in cities. In the present research, the focus is on the Konstantinidis stream and its surrounding area, located in Thessaloniki, Greece. More specifically, the main research question of this paper is how a stream, currently in a degraded state, can be integrated into the current open and green spaces of an area, contributing to the formation of a multifunctional open-space network that will provide recreational opportunities for users of all ages. Methodologically, a combination of research tools was used. First, a spatial analysis of the existing condition of the study area was carried out, which resulted to a series of maps presenting the planning and physical attributes of the neighborhood around the stream and of the existing open spaces. Second, field observation documented the condition of open spaces and usage patterns. Furthermore, and for a better understanding of the physiognomy of the area, a questionnaire survey was conducted, where residents were asked to rate the open and green spaces of their neighborhood. Thus, insightful information was extracted on how the residents/users of the area evaluate and perceive green and open spaces and local landmarks, which physical spatial factors affect their quality of life most and how they prioritize problems regarding green space. Based on an overall evaluation of the problems of the area and considering also the residents’ suggestions for its improvement, an integrated regeneration proposal was designed with the scope of integrating the stream area and providing opportunities for multiple uses and activities in the proposed green and public spaces network.